2015
DOI: 10.1371/journal.pone.0132819
|View full text |Cite
|
Sign up to set email alerts
|

The Neurophysiology of Language Processing Shapes the Evolution of Grammar: Evidence from Case Marking

Abstract: Do principles of language processing in the brain affect the way grammar evolves over time or is language change just a matter of socio-historical contingency? While the balance of evidence has been ambiguous and controversial, we identify here a neurophysiological constraint on the processing of language that has a systematic effect on the evolution of how noun phrases are marked by case (i.e. by such contrasts as between the English base form she and the object form her). In neurophysiological experiments ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
63
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(67 citation statements)
references
References 44 publications
(48 reference statements)
4
63
0
Order By: Relevance
“…Interestingly, in their neurophysiological study of language processing, Bickel et al (2015) found that listeners have a bias toward interpreting the first unmarked noun phrase in a sentence as an agent, which they take to mean that there is a processing bias/preference for accusative case-marking systems, over ergative case-marking systems. Recall from Section What Can Language Variation Tell Us?…”
Section: Genes and Geographymentioning
confidence: 99%
See 2 more Smart Citations
“…Interestingly, in their neurophysiological study of language processing, Bickel et al (2015) found that listeners have a bias toward interpreting the first unmarked noun phrase in a sentence as an agent, which they take to mean that there is a processing bias/preference for accusative case-marking systems, over ergative case-marking systems. Recall from Section What Can Language Variation Tell Us?…”
Section: Genes and Geographymentioning
confidence: 99%
“…The experimental design in Bickel et al's (2015) study is from the perspective of the listener, rather than the speaker. Even though the listener may show a preference for accusative marking, as it brings about disambiguation more rapidly, intransitive absolutive structures may require less effort on the part of the speaker.…”
Section: Genes and Geographymentioning
confidence: 99%
See 1 more Smart Citation
“…Typology-processing links are often based on an implicit assumption that processing mechanisms are the same universally, though this of course remains to be empirically demonstrated (for encouraging progress, see, e.g. Bickel et al, 2015;Dediu & Ladd, 2007, Fedzechkina, Jaeger, & Newport, 2012Fedzechkina, Newport, & Jaeger, submitted;Futrell, Mahowald, & Gibson, in press;Gildea & Temperley, 2010;Gildea & Jaeger, submitted, Graff & Jaeger, 2009;Piantadosi, Tily, & Gibon, 2011). 7. Our use of the term "Phrase Structure theories" is a label of convenience and is not meant to imply that all phrase structure grammars necessarily postulate a universal configurational subject position (thanks to Juergen Bohnemeyer (p.c.)…”
Section: Conclusion and Looking Forwardmentioning
confidence: 99%
“…Indeed, if core knowledge information is biologically fundamental, its prompt communication must be in some way advantageous. Interestingly enough, core knowledge information would be so relevant to shape the core structure of human languages (Bickel, Witzlack-Makarevich, Choudhary, Schlesewsky, & Bornkessel-Schlesewsky, 2015;Christiansen & Chater, 2008;Franzon, Zanini, & Rugani, 2018;Strickland, 2017). To what extent is this true for numerical knowledge?…”
Section: Introductionmentioning
confidence: 99%